CAMPOS RUPESTRES AND VEGETATION ON GRANITIC INSELBERGS IN EASTERN MINAS GERAIS, BRAZIL FOUR NEW SPECIES OF PLEROMA (MELASTOMATACEAE) FROM. (2022) - Goldenberg, R.; Gonella, P. M.; Meyer, F. S.
No abstract available